Women Who Taught : Perspectives on the History of Women and Teaching - Theobald, Marjorie R.; Prentice, Alison L. (Book collections on Project MUSE., 1991)
In an era when women are moving into so many areas of the labour force, we all remember some of the first working women we ever encountered: 'women teachers, ' as they were too often known. The impact of women on education has been enourmous throughout the English-speaking world. It has also been ignored, for the most part, by mainstream historians of education. Alison Prentice and Marjorie R. Theobald have addressed this omission by bringing together a wide range of essays by feminist historians on the role of women in education at all levels, in Canada, Australia, Britain, and the United States. All the essays were ground-breaking when first published. Among the subjects they explore are the experience of women in private, or domestic, schooling and the rigours of teaching as single women in remote areas. Other essays discuss the impact on women's working schools in the nineteenth century; the growth of professional teachers' organizations; and the blurring of public and private in the lives of twentieth-century teachers. The editors provide an introduction that traces the growth of the emerging field of the history of women in teaching and identifies new directions currently developing. A bibliography offers further resources.